Strategi Internalisasi Nilai Antikorupsi Bagi Peserta Didik - Agustina, Restika; Gade, Syabuddin (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2025)
This study aims to analyze strategies for internalizing anti-corruption values among students as an effort to build an anti-corruption culture within the education system. This research employs a qualitative approach using library research methods, drawing data from relevant scientific literature such as books, journals, and academic articles. The findings indicate that the internalization of anti-corruption values can be implemented through the integration of anti-corruption education into the school curriculum, the application of Problem-Based Learning (PBL), the development of thematic teaching modules, and the habituation of integrity and honesty values in daily school activities. Furthermore, anti-corruption education plays a vital role in fostering legal awareness and shaping students’ character to become honest, responsible, and integrity-driven individuals. Supporting factors such as a strong legal system, transparency, civil society participation, and an ethical organizational culture enhance the effectiveness of this internalization process. Therefore, anti-corruption education is a strategic step toward building a young generation with integrity, strong moral character, and commitment to eradicating corruption in Indonesia.